Spectral weight suppression in response functions of ultracold fermion-boson mixtures - Ji, Kai; Komnik, Andreas (Physical review, 2016)
We study the dynamical response of ultracold fermion-boson mixtures in the Bogoliubov regime, where the interactions between fermionic impurities and bosonic excitations (phonons) are described by an effective Fröhlich model under the Bogoliubov approximation. A characteristic suppression of the single-particle spectral weight is found in the small-momentum region where the impurity band and phonon mode intersect. Using a diagrammatic technique we compute the Bragg spectra as well as the momentum-dependent force-force correlation function. We find that both of them are heavily affected by the spectral weight suppression effect at low impurity densities in both one- and two-dimensional systems. We show that the spectral weight suppression feature in Bragg spectra, which was previously found in quantum Monte Carlo simulations and which cannot be recovered by the random phase approximation, can be accurately reproduced with the help of vertex corrections.
Gesehen am 06.05.2020